Rural Development Policies and Sustainable Land Use in the Hillside Areas of Honduras Survey, 2001-2002 - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
The survey was a research collaboration between International Food Policy Research Institute (IFPRI), Wageningen University and Research Center (WUR), and the National Program for Sustainable Rural Development (PRONADERS) of the Honduran Ministry of Agriculture and Livestock (SAG).The data were collected at three levels: farm household, parcel (distinguished by tenure status), and plot (distinguished by land use type). The survey contains a total of 376 farms, 1066 parcels, and 2143 plots. The survey collected information about household composition, education, asset ownership, labor use, sources of income, sales of crop and livestock products, participation in credit markets, membership of organizations, participation in training and extension, collective action and others at the farm level. The survey also collected information about cropping patterns, crop yields, and technology use including use of inputs at the plot level and land tenure, conservation practices, and conservation investments at the parcel level. In order to better understand the performance of the farm enterprise, the survey also collected detailed biophysical data for a sample of two plots on each farm including landscape attributes, size, type of soil parent material, erosion status, and presence of physical conservation structures. Soil samples were also taken and analyzed in a local soil laboratory resulting in data regarding pH, nutrient content, organic matter content, and soil texture. These data were mainly used for the calculation of water availability, soil fertility, and erosion risk which together served as a basis for soil suitability ratings. Finally, the survey data were supplemented by adding secondary information regarding rainfall, population density, and road density. The raw data are available in Access format and in SPSS format.